The Use of Irony and Satire in Contemporary British Poetry: A Study of Simon Armitage and Carol Ann Duffy - Dahham, Omer Ahmed (Integrated Journal for Research in Arts and Humanities, 2024)
This article focuses on studying how Simon Armitage and Carol Ann Duffy incorporate irony and satire in their poetry. The poems selected for analysis from Armitage's collection include 'Kid', 'Killing Time', and 'Thank you for waiting', while Duffy's chosen poems are 'The Little-Red Cap', 'Mrs. Midas', and 'Anne Hathaway'. By closely examining these poems, it becomes evident that both authors skillfully employ irony and satire to enhance their literary works. The article adopts an analytical approach, employing methods of comparison and analysis to explore this aspect.